Analisis hubungan pengetahuan, sikap, dan persepsi risiko dengan perilaku pencegahan komplikasi pada pasien diabetes melitus tipe 2 berdasarkan health belief model - Julia Vania Felicya Bahter; Bernabas Harold Ralph Kairupan; Jehosua Samratson Victor Sinolungan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a chronic disease caused by impaired insulin utilization or insufficient insulin production, resulting in hyperglycemia and an increased risk of complications such as cardiovascular disease, kidney disorders, retinopathy, and neuropathy. The control and prevention of complications depend not only on medical therapy but also on patients' self-care behaviors. Maria Walanda Maramis Regional General Hospital is required to implement health education through the Hospital Health Promotion Program in accordance with the Minister of Health Regulation Number 44 of 2018. However, its implementation still faces several challenges. Purpose: To analyze the relationship between knowledge, attitude, and risk perception with T2DM complication prevention behaviors in patients. Method: This analytic observational study with a cross-sectional approach was conducted at Internal Medicine Polyclinic, Maria Walanda Maramis Regional Hospital, December 2025 to January 2026. A total of 103 respondents were selected using consecutive sampling. Data were collected using structured questionnaires covering knowledge, attitude, risk perception (Champion’s HBM Scale), and T2DM complications prevention behaviors. Data were analyzed using univariate analysis, bivariate analysis(Chi-Square), and multivariate analysis (ordinal logistic regression). Results: There was a significant relationship between attitude and T2DM complication prevention behaviors (p = 0.004). There was no significant relationship between knowledge level (p = 0.066) or risk perception (p = 0.421) and prevention behaviors. Multivariate analysis confirmed that attitude was the most dominant factor (p = 0.007, OR = 0.066), with a variable contribution of 24.2% (Nagelkerke R² = 0.242). Conclusion: Increasing knowledge alone is insufficient to drive behavioral change. Complication preventive behavior is the outcome of a complex psychological process. Therefore, health interventions should not only focus on providing information but also on fostering positive attitudes, increasing motivation, and strengthening self-efficacy so that individuals can consistently adopt preventive behaviors. Suggestion: Future research should examine other relevant factors such as self-efficacy, family support, and psychosocial factors, as well as utilize a longitudinal design to establish stronger causal relationships. Keywords: Attitudes; Complications Prevention; Diabetes Mellitus Type 2; Health Belief Model; Knowledge; Risk Perception.